2009
DOI: 10.1021/cm901472x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Fabrication of Silica and Silica/Metal Hybrid Microtubes

Abstract: This paper describes a novel and simple method to fabricate silica and silica/metal hybrid microtubes of very high aspect ratio via self-rolling of polymer layers. A trilayer of poly(dimethylsiloxane) (PDMS)/polystyrene (PS)/poly(4-vinylpyridine) (P4 VP) self-rolled into microtubes, when exposed to a solvent selective for P4 VP chains, because of the strain generated by the swelling of P4 VP layer. Oxidative pyrolysis of the polymer tubes at 700 °C removes all the organic part of the tube and converts PDMS int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Luchnikov demonstrated that polystyrene-poly(4 vinyl pyridine) bilayer [24c] as well as polystyrene-poly(4 vinyl pyridine)-polydimethylsiloxane trilayer [29] are able to roll at low pH when poly(4-vinylpyridine) is protonated and swells in water. Use of layers with 2D gradient of thickness allowed thorough investigation of folding [30].…”
Section: Ph Responsivementioning
confidence: 99%
See 1 more Smart Citation
“…Luchnikov demonstrated that polystyrene-poly(4 vinyl pyridine) bilayer [24c] as well as polystyrene-poly(4 vinyl pyridine)-polydimethylsiloxane trilayer [29] are able to roll at low pH when poly(4-vinylpyridine) is protonated and swells in water. Use of layers with 2D gradient of thickness allowed thorough investigation of folding [30].…”
Section: Ph Responsivementioning
confidence: 99%
“…Deposition of patterned metal on the polymer bilayer allowed fabrication of self-rolled tubes with patterned conductive inner wall [24c]. In another example, pyrolysis of polystyrene-poly(4-vinyl pyridine)-polydimethylsiloxane trilayer [29] were used for fabrication of silica tubes. Gracias used self-folding polymers films were used to fabricate self-assembled curved microfluidic networks ( Fig.…”
Section: Properties and Applications Of Self-folding Filmsmentioning
confidence: 99%
“…This opens the way for the fabrication of 3D micro‐objects that otherwise cannot be realized. In this section, we describe experiments regarding the fabrication of inorganic microtubes and composite organic–inorganic microtubes 11, 20–21…”
Section: Composite Polymer‐metal and Ceramic Microtubes Produced Vmentioning
confidence: 99%
“…We also adopted the self-rolling phenomena of polymer layers to produce silica and silica/metal hybrid tube [12][13] . A thin film of PDMS was rolled with the P4VP/PS bilayer resulting in the formation of PDMS/P4VP/PS trilayer polymer tube.…”
Section: Hybride Tubesmentioning
confidence: 99%